The Secrets of Successful Selling / New, updated Edition - Adams Tony (Management Books 2000 Ltd, 1997)
A lively, practical book that gives straightforward and down-to-earth advice on the basic and not-so-basic principles of salesmanship. Preface, Prologue, The Secrets of selling into the Home, The Secrets of Selling to Retailers, The Secrets of Selling to Businesses, The Secret of Successful Salesmanship, Conclusion.